2012
DOI: 10.1186/cc11403
|View full text |Cite
|
Sign up to set email alerts
|

Regional citrate anticoagulation in cardiac surgery patients at high risk of bleeding: a continuous veno-venous hemofiltration protocol with a low concentration citrate solution

Abstract: IntroductionRegional citrate anticoagulation (RCA) is a valid option in patients at high risk of bleeding who are undergoing continuous renal replacement therapy (CRRT). The aim of this study was to evaluate, in critically ill patients with severe acute kidney injury following cardiac surgery, the efficacy and safety of RCA-continuous veno-venous hemofiltration (CVVH) using a low concentration citrate solution.MethodsIn high bleeding-risk cardiac surgery patients, we adopted, as an alternative to heparin or no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
95
1
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 71 publications
(110 citation statements)
references
References 29 publications
12
95
1
2
Order By: Relevance
“…Several studies comparing citrate-based protocols with heparin-based protocols have reported better filter survival and/or fewer bleeding events during RCA (14)(15)(16)(17)(18)(19). Two separate meta-analyses, including six randomized trials comparing RCA with systemic anticoagulation with heparin, confirmed a significant decrease of bleeding events in the citrate arm (70,71); however, they provided slightly different results about filter survival.…”
Section: Safety and Efficacy Of Rcamentioning
confidence: 86%
See 4 more Smart Citations
“…Several studies comparing citrate-based protocols with heparin-based protocols have reported better filter survival and/or fewer bleeding events during RCA (14)(15)(16)(17)(18)(19). Two separate meta-analyses, including six randomized trials comparing RCA with systemic anticoagulation with heparin, confirmed a significant decrease of bleeding events in the citrate arm (70,71); however, they provided slightly different results about filter survival.…”
Section: Safety and Efficacy Of Rcamentioning
confidence: 86%
“…The physiologic sodium content of isotonic solutions allows RCA CVVH or RCA CVVHDF without the need of a low-sodium replacement fluid and/ or dialysate (Table 1). In protocols using citrate-buffered replacement solutions, the buffer supply derives from citrate (predilution CVVH) or citrate and bicarbonate in various proportions (predilution and postdilution CVVH and CVVHDF) in relation to the composition and the combination of the solutions that are used (14,19,50,62,(64)(65)(66)(67). A simplification on the basis of the use of solutions with an appropriately low citrate concentration allows RCA CRRT as CVVH in the predilution-only modality (19,50).…”
Section: Low-concentration Citrate Solutions (Isotonic In Sodium)mentioning
confidence: 99%
See 3 more Smart Citations